A Comprehensive Study on the Antimicrobial Properties of Resveratrol as an Alternative Therapy. (16th March 2021) - Abedini, Ehsan; Khodadadi, Ehsaneh; Zeinalzadeh, Elham; Moaddab, Seyyed Reza; Asgharzadeh, Mohammad; Mehramouz, Bahareh; Dao, Sounkalo; Samadi Kafil, Hossein
Abstract : Resveratrol is a polyphenolic antioxidant whose possible health benefits include anticarcinogenic, antiaging, and antimicrobial properties that have gained significant attention. The compound is well accepted by individuals and has been commonly used as a nutraceutical in recent decades. Its widespread usage makes it essential to study as a single agent as well as in combination with traditional prescription antibiotics as regards to antimicrobial properties. Resveratrol demonstrates the action of antimicrobials against a remarkable bacterial diversity, viruses, and fungus. This report explains resveratrol as an all-natural antimicrobial representative. It may modify the bacterial virulence qualities resulting in decreased toxic substance production, biofilm inhibition, motility reduction, and quorum sensing disturbance. Moreover, in conjunction with standard antibiotics, resveratrol improves aminoglycoside efficacy versus Staphylococcus aureus, while it antagonizes the deadly function of fluoroquinolones against S. aureus and also Escherichia coli . The present study aimed to thoroughly review and study the antimicrobial potency of resveratrol, expected to help researchers pave the way for solving antimicrobial resistance.